Effect of prenatal exposure to per- and polyfluoroalkyl substances on childhood allergies and common infectious diseases in children up to age 7 years: The Hokkaido study on environment and children's health - Yu Ait Bamai; Houman Goudarzi; Atsuko Araki; Emiko Okada; Ikuko Kashino; Chihiro Miyashita; Reiko Kishi (Environment International, 2020)
Per- and polyfluoroalkyl substances (PFAS) are widely used bio-accumulative chemicals in many industrial and household products. Experimental studies reported that exposure to PFAS results in immunotoxicity. We have previously reported that prenatal exposure to PFAS decreased the risk of allergies, while it increased the risk of infectious diseases at ages 2 and 4 years. However, it remains unclear whether the adverse effects of PFAS on allergies and infectious diseases continue until a reliable age of diagnosing allergies. This study aimed at investigating the effects of prenatal exposure to PFAS on the prevalence of allergies and infectious diseases in children up to age 7, from the Hokkaido Study.Among mother-child pairs enrolled in the Hokkaido study and followed up until the age of 7 years, 2689 participants with maternal PFAS, 1st trimester of pregnancy and 7-year-old questionnaire survey data were included in this study. Eleven PFAS in the 3rd-trimester plasma were measured using ultra-performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry. Wheeze, rhino-conjunctivitis, and eczema were defined using the International Study of Asthma and Allergies on Childhood (ISAAC) questionnaire. History childhood infectious diseases diagnosed by a doctor was assessed by a mother-reported questionnaire at child’s age 7. The relative risk of childhood allergies was calculated by generalized estimating equation models. The odds ratio of an episode of infectious diseases was calculated by logistic regression analysis, adjusted for potential confounders.The prevalence of various allergies and infectious diseases was: wheeze, 11.9%; rhino-conjunctivitis, 11.3%; eczema, 21.0%; chickenpox, 61.5%; otitis media, 55.7%; pneumonia, 30.6%; and respiratory syncytial virus infection, 16.8%. Prenatal exposure to perfluorooctanoic acid, perfluorodecanoic acid (PFDA), and perfluoroundecanoic acid (PFUnDA) was inversely associated with rhino-conjunctivitis, while that for perfluorooctanoate (PFOA), perfluorooctane sulfonate, PFUnDA, perfluorododecanoic acid (PFDoDA), and perfluorotridecanoic acid was inversely associated with eczema. For infectious diseases, PFDA and PFDoDA were associated with increased risk of pneumonia and PFOA was associated with increased risk of RSV infection among children not having any siblings (only-one-child).Our results corroborate the hypothesis on immunosuppressive and immunomodulating effects of PFAS on allergies and infectious diseases in children. These effects observed previously at 2 and 4 years continued until the age of 7 years. However, additional studies assessing inflammatory biomarkers along with ISAAC questionnaires, doctor-diagnosed allergies, and longer follow-ups are necessary to better assess the effects of exposure to chemicals on human immune outcomes.